Efficacy of Dog Training With and Without Remote Electronic Collars vs. a Focus on Positive Reinforcement - China, Lucy; Mills, Daniel S.; Cooper, Jonathan J. (Frontiers in Veterinary Science, 2020)
We assessed the efficacy of dog training with and without remote electronic collars compared to training with positive reinforcement. A total of 63 dogs with known off-lead behavioural problems such as poor recall were allocated to one of three training groups (each n=21), receiving up to 150 minutes of training over five days to improve recall and general obedience. The 3 groups were: E-collar - manufacturer-nominated trainers who used electronic stimuli as part of their training program; Control 1 - the same trainers following practices they would apply when not using electronic stimuli; and Control 2 - independent, professional trainers who focused primarily on positive reinforcement for their training. Data collection focused on dogs’ response to two commands: “Come” (recall to trainer) and “Sit” (place hindquarters on ground). These were the two most common commands used during training, with improving recall being the target behaviour for the subject dogs. Measures of training efficacy included number of commands given to elicit the response and response latency. Control 2 achieved significantly better responses to both “Sit” and “Come” commands after a single instruction in the allocated time. These dogs also had shorter response latencies than the E-collar group. There was no significant difference in the proportion of command disobeyed between the three groups, although significantly fewer commands were given to the dogs in Control 2. There was no difference in the number of verbal cues used in each group, but Control 2 used fewer hand and lead signals, and Control 1 made more use of these signals than E-collar group. These findings refute the suggestion that training with an E-collar is either more efficient or results in less disobedience, even in the hands of experienced trainers. In many ways, training with positive reinforcement was found to be more effective at addressing the target behaviour as well as general obedience training. This method of training also poses fewer risks to dog welfare and quality of the human-dog relationship. Given these results we suggest that there is no evidence to indicate that E-collar training is necessary, even for its most widely cited indication.